2009
DOI: 10.1016/j.jalgebra.2009.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Depth two Hopf subalgebras of a semisimple Hopf algebra

Abstract: A depth two Hopf subalgebra K of a semisimple Hopf algebra H is shown to be a normal Hopf subalgebra. On the one hand, we prove this using Galois theory of quantum groupoids. On the other hand, we give a second proof using character theory of semisimple Hopf algebras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…By means of general theory in one direction and Mackey theory in the other, depth two subgroup is shown to be precisely a normal subgroup [10]. (A similar statement is true for semisimple Hopf C -subalgebras [4].) In this paper we generalize this approach to depth two subgroup to a semisimple subalgebra pair, giving a condition in terms of inclusion matrix [7], which is the same as a induction-restriction table [1] up to a permutation change of basis.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…By means of general theory in one direction and Mackey theory in the other, depth two subgroup is shown to be precisely a normal subgroup [10]. (A similar statement is true for semisimple Hopf C -subalgebras [4].) In this paper we generalize this approach to depth two subgroup to a semisimple subalgebra pair, giving a condition in terms of inclusion matrix [7], which is the same as a induction-restriction table [1] up to a permutation change of basis.…”
Section: Introductionmentioning
confidence: 75%
“…There it is determined that a tower of three group algebras corresponding to the subgroup chain G ≥ H ≥ K is depth-3 if the normal closure K G (of K in G) is contained in H (and shown above in Theorem 1.1 to be a characterization of depth-3 tower of finite groups). In [10] it is shown that, with k = C and G a finite group, the group algebra A of G is depth two over subgroup algebra B of H if and only if H is a normal subgroup of G. This normality result for depth two subalgebras is extended to semisimple Hopf algebras over an algebraically closed field of characteristic zero in [4].…”
Section: Proposition 113 Let B Be a Hopf Subalgebra Of A Thenmentioning
confidence: 96%
“…Depth two is an algebraic notion for noncommutative ring extensions with a Galois theory associated to it [14,15]. If applied to a subalgebra pair of quantum algebras, depth two is a notion of normality that extends ordinary normality for subgroups and Hopf subalgebras [17,13,7]. A Hopf subalgebra K is normal in a finite dimensional Hopf algebra H if and only if H is a depth two ring extension of K: see [3] for this theorem and how it generalizes to faithfully flat, finitely generated projective Hopf algebra extensions over a commutative base ring as well as one-sided versions of normality, depth two and Hopf-Galois extension.…”
Section: Introductionmentioning
confidence: 99%

On subgroup depth

Burciu,
Kadison,
Kuelshammer
2009
Preprint
Self Cite